Vulnerable areas and intraoperative management strategies of transanal total mesorectal excision - Zhao Shidong; Ye Yingjiang; Shen Zhanlong (结直肠肛门外科)
Transanal total mesorectal resection (taTME) has been developed and practiced for more than 10 years and has been recognized by more and more colorectal surgeons due to its good surgical vision during the radical resection of low rectal cancer. However, due to its “caudal to cranial” operating perspective, colorectal surgeons need to correctly understand the relevant anatomical levels and markers in order to achieve higher surgical quality. In this paper, the five vulnerable areas of taTME, including anal sphincter, anterior sacral vein, neurovascular bundle, posterior branch of pelvic plexus and male urethra, as well as relevant operation points, were described, and intraoperative management strategies were proposed.